Strategies of phage contamination prevention in industry - Marcin Los (Open Journal of Bacteriology - Peertechz Publications, 2020)
Phages are potential cause of failure of bacteria-driven production processes. In this paper some observations arising from the experience of the author, concerning the strategies of phage prevention, adopted by different industries is described. The exact choice of the strategy is usually driven by the economy, but also by the regulatory aspects of the operation. The less regulatory or economic freedom industry offer, the more attention is payed to the improvement of equipment and process hygiene.